An Insight into the Genesis of Hypohidrotic Ectodermal Dysplasia in a Case Report - Kiran Kumar; Devi Charan Shetty; Mahima Dua; Amit Dua; Raghu Dhanapal (Case Reports in Dentistry)
Hypohidrotic (anhidrotic) ectodermal dysplasia (HED) is a congenital syndrome characterized by sparse hair, oligodontia, and reduced sweating. It is estimated to affect at least one in 17000 people worldwide. We report a rare case of HED in a 14-year-old male child patient which extraorally manifested as alopecia, scanty eyebrow and eye lashes, frontal bossing, depressed nasal bridge, and full and everted lips. Intraoral examination revealed complete anodontia of the deciduous teeth and partial anodontia of the permanent teeth. It is usually inherited as an X-linked recessive trait caused by mutation in any of the three EDA pathway genes. X-linked and autosomal recessive forms are phenotypically similar; thus, identification of carriers of partial forms of the disorder in their families is the key to clarifying intrafamilial genetic transmission.